Applicability of the 48/6 Model of Care as a Health Screening Tool, and its Association with Mobility in Community-Dwelling Older Adults - Uhm, Kyeong Eun; Oh-Park, Mooyeon; Kim, Yoon-Sook; Park, Jae-Min; Choi, Jaekyung; Moon, Yeonsil; Han, Seol-Heui; Hwang, Jeong Hae; Lee, Kun Sei; Lee, Jongmin (Journal of Korean medical science, 2020)
The 48/6 Model of Care is an integrative care initiative for improving the health outcomes of hospitalized older patients; however, its applicability in community-dwelling older adults as a health screening tool has not been investigated. The present study aimed to examine the applicability of this model, prevalence of dysfunction in 6 care areas, and its relationship with self-reported mobility in community-dwelling older adults. This was a cross-sectional survey study of community-dwelling adults aged 65 or older. Participants were screened for problems using 9 items corresponding to the 6 care areas of the 48/6 Model of Care (cognitive functioning, functional mobility, pain management, nutrition and hydration, bladder and bowel management, and medication management). Mobility was assessed via the Life-Space Assessment (LSA). We examined the correlation between each screening item and the LSA. A total of 444 older adults (260 women, 58.6%) participated. The mean number of health problems was 2.3 ± 2.1, with the most common being pain, cognitive impairment, and urinary incontinence. These problems and LSA scores were significantly different by age groups. A multiple regression analysis showed that polypharmacy (β = -10.567, < 0.001), dysphagia (β = -9.610, = 0.021), and pain (β = -7.369, = 0.004) were significantly associated with life-space mobility after controlling for age. The 48/6 Model of Care is applicable to community-dwelling older adults, who show high prevalence of dysfunction in the 6 care areas. This study supports the role of the model in screening for the health status of older adults living in the community, and in estimating mobility.